Acute Neuromuscular and Hormonal Responses to Resistance Exercise Using Variable External Resistance Loading - Aboodarda, S.J.; Ibrahim, F.; Mokhtar, A.H.; Thompson, M.W.; Behm, D.G. (American Society of Exercise Physiologists, 2012)
Variable resistance training (VRT) such as that employed by equipment that utilizes asymmetrical cams or pulleys (ASYM CAM) (e.g., Nautilus Machines) and elastic resistance (ELASTIC) are commonly used by athletes and fitness enthusiasts. However, the use of ELASTIC in high intensity training protocols has been controversial due to the limitation of providing a relatively low external force. The purpose of this study was designed to quantify and compare the acute responses in electromyogram signals (EMG) and the concentration of serum growth hormone ([GH]), testosterone ([T]), and lactate ([LA]) following fatiguing knee extension exercise with ELASTIC and ASYM CAM. In a counterbalanced cross-over study, nine male (21.08 ± 6.2 yrs) recreationally active subjects completed 5 sets of 10-RM knee extension exercise with ELASTIC and ASYM CAM with 3 wks of no training between experimental conditions. Blood sampling, maximum voluntary contraction (MVC) and EMG were recorded before, immediately, 15, 30, and 60 min after the termination of the exercise bout. The average of applied forces with ASYM CAM was significantly higher than ELASTIC (362 ± 34.2 N vs. 266.73 ± 58.56 N; P = .00) across the 5 sets of dynamic exercises. However, the average force and mean amplitude of MVC as well as the [GH], [T] and [LA] demonstrated no significant difference between the two types of exercise either in the pretest or during the recovery period (all P>0.05). Contrary to the traditional approach of using ELASTIC, which is for early rehabilitation purposes, the findings of the present study suggest ELASTIC is an acceptable exercise device for high intensity resistance training in the final stages of rehabilitation as well as athletic conditioning.